Distinguishing Unilateral from Bilateral Primary Aldosteronism: The Reliability of the Posture Test and the Success Rate of Adrenal Venous Sampling in Iceland - Gunnarsdóttir, Hrafnhildur; Guðmundsson, Jón; Birgisson, Guðjón; Sigurjónsdóttir, Helga Ágústa (Hormone and Metabolic Research, 2025)
Primary aldosteronism is a common cause of hypertension. Distinguishing between unilateral and bilateral primary aldosteronism is mandatory and remains a challenge. The upright posture test has been debated, whereas adrenal venous sampling remains the gold standard for subtyping. We conducted a retrospective nationwide study of 49 adult patients who underwent both the posture test and adrenal venous sampling and were diagnosed with primary aldosteronism in Iceland between 2007 and 2016. The diagnostic utility of the posture test in predicting adrenal venous sampling-confirmed laterality was assessed, along with an adrenal venous sampling success rate. The posture test demonstrated 81% sensitivity and 45% specificity for detecting bilateral primary aldosteronism. The optimal s-aldosterone increase cut-off for detecting bilateral primary aldosteronism using the posture test was 74%, yielding 59% specificity. The adrenal venous sampling success rate was 86%, and adrenal computed tomography correctly predicted laterality in all patients under 35 years of age. These findings indicate that the posture test can be a useful tool, although its limited specificity reduces its clinical utility in centers with access to reliable adrenal venous sampling. The high adrenal venous sampling success rate in Iceland reflects expertise in the procedure. Adrenal computed tomography appeared to be accurate in younger patients, supporting The Endocrine Society guideline recommendations.
Keywords: adrenal CT; posture test; adrenalectomy; AVS success rate; primary aldosteronism; adrenal venous sampling